The potential of Polyurethane in producing a relief painting / Mohd Ali Azraie Bebit, Suzlee Ibrahim and Iqbal Jaapar - Bebit, Mohd Ali Azraie; Ibrahim, Suzlee; Jaapar, Iqbal (Faculty of Art and Design, 2019)
This research is exploring the potential use of the polyurethane element and technique to produce three-dimensional forms as an alternative to canvas artworks. Canvas, being the conventional medium for painting has the limitation in producing relief artworks. Due to this reason, polyurethane as the potential property of petroleum-based material is explored as a new medium of artwork. Exploration of materials creates new medium for artworks and allows artists to impose various techniques onto the material. Exploration of new materials will challenge and enhance the creative process of producing an artwork. Thus, this research is interested in experimenting with polyurethane with various techniques which may be useful for manipulating the material. The effect and results are not always as expected due to accidental effects encountered during the process. Therefore, the use of different techniques on polyurethane has given satisfactory or non-satisfactory results due to its appearance on the artwork. Through simple tests, it is proven that polyurethane has the potential character as relief artwork. It is stable, durable and flexible. In conclusion, polyurethane is suitable to be used as an alternative to canvas for producing relief artworks.